EFFECT OF SACUBITRIL/VALSARTAN ON NATRIURESIS, DIURESIS AND BLOOD PRESSURE IN HYPERTENSIVE PATIENTS - Zh. D. Kobalava; S. V. Villevalde; I. A. Meray; O. I. Lukina (Рациональная фармакотерапия в кардиологии, 2017)
Aim. To study the effect of sacubitril/valsartan compared with valsartan on natriuresis, diuresis, blood pressure (BP) and the level of biomarkers in hypertensive patients.Material and methods. Hypertensive patients (n=16) received sacubitril/valsartan 400 mg QD or valsartan 320 mg QD for 7 days in a double-blind,-randomized, cross-over study. The change in 24-hour diuresis and natriuresis, fractional urinary sodium excretion, and BP level have been studied, as-well as soluble biomarkers: cyclic guanosine monophosphate (cGMP), plasma brain natriuretic peptide (BNP), mid-regional precursor of the atrial natriuretic-peptide (MR-proANP) and the N-terminal precursor of the brain natriuretic peptide (NT-proBNP).Results. The trend toward higher levels of 24-hour natriuresis on Day 1 (21%, p=0.068) was found in the sacubitril/valsartan group compared to-valsartan one. Fractional sodium excretion was significantly higher in the sacubitril/valsartan group on Day 1 after 6 hours (50%, p=0.004) and subsequent-samples up to 12 hours; the maximum effect was achieved 2-4 hours after taking the medication (mean value 2.08, p=0.005). Sacubitril/valsartan-therapy compared with valsartan therapy was associated with a significant increase in 24-hour diuresis on Day 1 (41%, p<0.05), but not on Day 7-(15%, p=0.134). Sacubitril/valsartan therapy, in contrast to valsartan therapy demonstrated a significant increase in 24 h cGMP urinary excretion-on Day 1 (95%, p<0.001) and Day 7 (83%, p=0.001). Sacubitril/valsartan lowered BP more effectively than valsartan [on Day 7, 12 hours after-taking the drug, the differences were13.6 mm Hg (p=0.004) for systolic and6.7 mm Hg (p=0.03) for diastolic BP. The decrease in the level of-NT-proBNP and MR-proANP in plasma and the transient increase in the level of BNP were found in the sacubitril/valsartan group. Both sacubitril/valsartan and valsartan therapies were well tolerated and safe.Conclusion. Sacubitril/valsartan therapy in hypertensive patients compared with valsartan therapy was associated with transient increase in natriuresis and diuresis, more pronounced decrease in BP and changes in biomarker levels reflecting persistent inhibition of neprilysin and decrease in myocardial wall tension.